Don’t blame women for low libido. Sexual sparks fly when partners do their share of chores – including calling the plumber - Buzwell, Simone; Johansen, Eva (The Conversation, 2022)
When a comic about “mental load” went viral in 2017, it sparked conversations about the invisible workload women carry. Even when women are in paid employment, they remember their mother-in-law’s birthday, know what’s in the pantry and organise the plumber. This mental load often goes unnoticed. Women also continue to do more housework and childcare than their male partners. This burden has been exacerbated over the recent pandemic (homeschooling anyone?), leaving women feeling exhausted, anxious and resentful. As sexuality researchers, we wondered, with all this extra work, do women have any energy left for sex?
Keywords: 2000 à aujourd'hui; 2020-2029; australie; charge mentale; discipline; désir; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; thématiques